Remarkable strength of CoCrFeNi high-entropy alloy wires at cryogenic and elevated temperatures. (December 2017) - Huo, Wenyi; Fang, Feng; Zhou, Hui; Xie, Zonghan; Shang, Jianku; Jiang, Jianqing
Abstract: CoCrFeNi high-entropy alloy wires containing nano-sized twins were produced by heavy cold-drawing process. The alloy wires exhibit high tensile yield strength of 1.2 GPa, as well as a considerably high percentage elongation (i.e., ductility) of 13.6% at 223 K. Such cryogenic and room temperature properties were found to result from the blockage of dislocation glide by primary and secondary nano-scale twin boundaries and, to less extent, by other dislocations. The high level of strength remained with the increase of temperature up to 923 K. The deformation mechanism of the cold-drawn wires was observed to be governed by dislocation slip and dynamic recovery at elevated temperatures. Graphical abstract: Tensile strength of cold drawn CoCrFeNi HEAs wire was higher than that of undeformed HEAs at elevated temperatures. It should be resulted from deformation-induced grain refinement, nano-twinning and dislocation.